Reflections on story-telling and creative-autobiographical-literary writing - Wolting, Stephan (Glottodidactica, 2019)
The aim of the text is to discuss some issues related to the academic principles of autobiographical writing and practical workshops aiming to improve intercultural, trans- and cross-cultural competences. We have to keep in mind that the significance of terms as narration, telling, storytelling particularly with regard to different academic contexts is growing. The study is based on different tried and tested writing exercises, on writing plays as flash-fiction, writing based on a model, so as to motivate and inspire the students, to produce their own creative, autobiographical and, in a broader sense, “literary works” and to take this into account for foreign language teaching